COINS OF HOPE: MODEL PENGAJARAN TENTANG UANG, KONSERVASI MORAL DAN KETERAMPILAN BERBICARA DESKRIPTIF DALAM BAHASA INGGRIS - Tusyanah, Tusyanah (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
Most students in Economics Faculty are not skillful in speaking English, so itneeds the active learning to encourage them to talk and improve their good characters.Therefore; I suggest the program of Coins of Hope to solve this problem. The problemof the study is: Does the Coins of Hope improve students’ speaking skills in Englishsubject and support the moral conservation at Semarang State University? It isexpected that the program of Coins of Hope is effective to improve students’ speakingskills at Descriptive text in English and also improve students’ characters.